If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(g + -3) + 5g = 0 Reorder the terms: 7(-3 + g) + 5g = 0 (-3 * 7 + g * 7) + 5g = 0 (-21 + 7g) + 5g = 0 Combine like terms: 7g + 5g = 12g -21 + 12g = 0 Solving -21 + 12g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 12g = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 12g = 0 + 21 12g = 0 + 21 Combine like terms: 0 + 21 = 21 12g = 21 Divide each side by '12'. g = 1.75 Simplifying g = 1.75
| 3=4x^(2/5) | | h-6u+7=-29 | | 6=2k-8k | | E(x)=0.0048x^3-0.0054x^2 | | 7(x-6)=5(x+2) | | 6b^2=42b-72 | | 7(8-9x)=0 | | 3x+9-5x+7-2x=20 | | 7y+45=y-3 | | -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x | | 2x+5(5x-1)=-113 | | 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 |